2020
DOI: 10.1186/s12882-020-01918-2
|View full text |Cite
|
Sign up to set email alerts
|

Healthy adult vegetarians have better renal function than matched omnivores: a cross-sectional study in China

Abstract: Background: An appropriate diet is an important determinant of kidney health. However, the association between vegetarian diets and renal function is unclear. We aimed to study the association between vegetarian diets and renal function in healthy adults. Methods: A total of 269 vegetarians and 269 sex-and age-matched nonvegetarian omnivores were enrolled in this cross-sectional study. Basic characteristics and daily dietary intakes were assessed by face-to-face interviews. Blood samples were collected, and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
1
3
1
Order By: Relevance
“…There has been limited evidence on comparisons of renal biomarkers between vegetarians and nonvegetarians, although several small studies have reported lower serum ( 51 ) or urinary creatinine ( 52 ) or lower blood urea nitrogen (a correlate of serum urea) ( 51 ) in vegetarians or vegans, for which large differences were found in our study. Similar to current findings, previous analyses in the UK EPIC-Oxford cohort have found that compared with meat eaters, fish eaters and vegetarians had lower concentrations of serum uric acid (also known as urate), whereas vegans had the highest concentrations ( 53 ), possibly due to their exclusion of dairy products and subsequently reduced excretion of uric acid ( 54 ).…”
Section: Discussioncontrasting
confidence: 59%
“…There has been limited evidence on comparisons of renal biomarkers between vegetarians and nonvegetarians, although several small studies have reported lower serum ( 51 ) or urinary creatinine ( 52 ) or lower blood urea nitrogen (a correlate of serum urea) ( 51 ) in vegetarians or vegans, for which large differences were found in our study. Similar to current findings, previous analyses in the UK EPIC-Oxford cohort have found that compared with meat eaters, fish eaters and vegetarians had lower concentrations of serum uric acid (also known as urate), whereas vegans had the highest concentrations ( 53 ), possibly due to their exclusion of dairy products and subsequently reduced excretion of uric acid ( 54 ).…”
Section: Discussioncontrasting
confidence: 59%
“…A study in Thailand revealed a significantly lower level of BUN, BUN/creatinine ratio and a lower urinary protein excretion rate in vegans compared to nonvegans, 21 while a recent cross‐sectional study in China reported that vegetarians had better kidney function parameters than nonvegetarians, also after adjustment for possible confounding factors. 22 In another cross‐sectional study on 55,113 participants from Taiwan, VD was significantly associated with lower prevalence of CKD, 23 and similar findings were reported in two prospective cohort studies after 6.1 years 24 and 24 years 25 of follow‐up.…”
Section: Discussionsupporting
confidence: 58%
“…There is evidence to suggest that dietary factors, particularly protein and the amino acid leucine, play a critical role in promoting muscle protein synthesis and preserving muscle mass [42,43]. Vegetarians have considerably lower serum creatinine concentrations than omnivores in numerous big cross-sectional investigations [44,45]. Interestingly, an animal study revealed that insufficient nutrition during the first half of pregnancy is associated with later metabolic abnormalities and favors a diabetogenic condition in the pregnant mother [46].…”
Section: Discussionmentioning
confidence: 99%